2012
DOI: 10.1371/journal.pone.0044515
|View full text |Cite
|
Sign up to set email alerts
|

Glacial History of a Modern Invader: Phylogeography and Species Distribution Modelling of the Asian Tiger Mosquito Aedes albopictus

Abstract: BackgroundThe tiger mosquito, Aedes albopictus, is one of the 100 most invasive species in the world and a vector of human diseases. In the last 30 years, it has spread from its native range in East Asia to Africa, Europe, and the Americas. Although this modern invasion has been the focus of many studies, the history of the species’ native populations remains poorly understood. Here, we aimed to assess the role of Pleistocene climatic changes in shaping the current distribution of the species in its native ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 81 publications
10
79
0
Order By: Relevance
“…Other studies of A. albopictus mitochondrial diversity also showed that native populations of this species harbor very low or no mitochondrial genetic diversity (Poretta et al, 2012). The pattern observed of genetic variation in populations of A. albopictus may be attributed to severe, repeated, or long periods of population bottlenecks that resulted in genetic variation losses because of random genetic drift (Nei et al, 1975;Birungi and Munstermann, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…Other studies of A. albopictus mitochondrial diversity also showed that native populations of this species harbor very low or no mitochondrial genetic diversity (Poretta et al, 2012). The pattern observed of genetic variation in populations of A. albopictus may be attributed to severe, repeated, or long periods of population bottlenecks that resulted in genetic variation losses because of random genetic drift (Nei et al, 1975;Birungi and Munstermann, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…In addition to ND5, analysis of mtDNA gene sequences including Cytb and COI has also been used to examine the phylogeography of Ae. albopictus (Mousson et al 2005, UsmaniBrown et al 2009, Kamgang et al 2011, Porretta et al 2012, Beebe et al 2013). Additionally, a recent study analyzing COI mtDNA variation strongly supports an Asian origin of Ae.…”
Section: Population Genetics and Establishment Of Ae Albopictus In Nmentioning
confidence: 99%
“…A combination of phylogenetic analyses with distribution models was used to reconstruct the spatial occurrence of A. albopictus during the Pleistocene [63]. Such combined approaches seem to be a promising effort to support future projections.…”
Section: Further Challenges For Risk Assessmentmentioning
confidence: 99%